2015
DOI: 10.1007/s00063-015-0118-8
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality in patients with cardiogenic shock treated with primary percutaneous coronary intervention and intra-aortic balloon counterpulsation

Abstract: This is the author's final version. The version of record may be found online at http://dx.doi.org/10.1007/s00063-015-0118-8. Please cite this version, Schwarz, B, Abdel-Wahab, M, Robinson, D R and Richardt, G (2016) Predictors of mortality in patients with cardiogenic shock treated with primary percutaneous coronary intervention and intra-aortic balloon counterpulsation. Medizinische Klinik -Intensivmedizin und Notfallmedizin, 111 (8

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…The comprehensive search yielded 1093 potentially relevant articles; after exclusion of duplicates and assessment of titles and/or abstracts, 29 articles were chosen for complete review. Finally, nine studies including 1348 patients met our inclusion criteria, published between 2005 and 2017 (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The comprehensive search yielded 1093 potentially relevant articles; after exclusion of duplicates and assessment of titles and/or abstracts, 29 articles were chosen for complete review. Finally, nine studies including 1348 patients met our inclusion criteria, published between 2005 and 2017 (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…The main characteristics of the included studies are presented in Table 1 and quality assessment results are described in Tables S2 and S3. Seven studies were observational studies, [21][22][23][24][25][26][27] and the remaining two were sub-analysis of randomized controlled trials. 20,28 Five of the eligible studies only enrolled patients who presented with STEMI, [22][23][24][25]27 and the remaining four included patients with non-STEMI.…”
Section: Eligible Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiogenic shock has been shown to represent the most serious complication in STEMI patients [8]. In patients with myocardial infarction and cardiogenic shock, the use of vasopressor agents, age, cardiac arrest, renal failure and counterpulsation balloon insertion, have been proved to represent independent predictors of in-hospital mortality [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with myocardial infarction and cardiogenic shock, the use of vasopressor agents, age, cardiac arrest, renal failure and counterpulsation balloon insertion, have been proved to represent independent predictors of in-hospital mortality [8,9]. A study reporting on 572 consecutive patients with cardiogenic shock and AMI, indicated that a more severe clinical profile and serious arrhythmia are associated with a higher mortality [9].…”
Section: Discussionmentioning
confidence: 99%